Tropical ecosystem multifunctionality assessment and insights for sustainable land management: a systematic literature review using the driver-pressure-state-impact-responses framework - Tabi Eckebil, Paule Pamela; Mintah, Frank; Bürgi, Matthias; Akinyemi, Felicia O.; Sonwa, Denis Jean; Ifejika Speranza, Chinwe (Frontiers in Forests and Global Change, 2025)
A systematic review of studies on tropical ecosystem multifunctionality (EMF) reveals the main factors influencing ecosystems’ ability to provide multiple functions and services. We examined forty publications to determine the methodological approaches used to assess the multifunctionality of tropical ecosystems. The DPSIR helped to identify the drivers, pressures, state, impacts and responses shaping EMF. Biophysical-based methods dominate in calculating multifunctional indices using average and threshold values, while the use of social science-based methods is low. Most identified drivers are direct, such as land-use change, whereas pressures arise from human activities and environmental stressors. Biotic and abiotic factors affecting ecological conditions directly impact human well-being. Most responses are concentrated at the national level and neglect the local level, particularly those policies that support integrated landscape approaches. The inadequate integration of social dimensions and local levels in EMF calls for holistic approaches that balance attention to social needs and ecosystem health, thereby enhancing sustainable land management.